1976
DOI: 10.1210/jcem-43-2-394
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic-Pituitary Function in Patients with Craniopharyngiomas

Abstract: Hypothalamic-pituitary function was investigated in 20 patients with craniopharyngioma, and all showed some degree of hypopituitarism. Pituitary-adrenal dysfunction was present in 50% of the patients whereas all but one had deficiencies of growth hormone and gonadotropin. Serum thyroxine was low in 13 patients, and in a further six there was an abnormal response of thyrotropin (TSH) to thyrotropin-releasing hormone (TRH). Prolactin levels were normal in over half the patients tested and only moderately elevate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
1

Year Published

1980
1980
2007
2007

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(14 citation statements)
references
References 18 publications
1
12
1
Order By: Relevance
“…In this study, all IGHD patients were of euthyroid state, but they showed delayed TSH responses to TRH as was seen also in 2ry GHD patients. This may indicate that IGHD patients have subclinical lesions in hypothalamic TRH neurons (Jenkins et al 1976 ;Okada et al 1978). Plasma PRL responses to TRH were also significantly delayed in IGHD and 2ry GHD patients.…”
Section: Discussionmentioning
confidence: 93%
“…In this study, all IGHD patients were of euthyroid state, but they showed delayed TSH responses to TRH as was seen also in 2ry GHD patients. This may indicate that IGHD patients have subclinical lesions in hypothalamic TRH neurons (Jenkins et al 1976 ;Okada et al 1978). Plasma PRL responses to TRH were also significantly delayed in IGHD and 2ry GHD patients.…”
Section: Discussionmentioning
confidence: 93%
“…Exaggerated and/or delayed TSH responses have been interpreted as being suggestive of hypothalamic lesions in several previous studies in both adults and children [4,5,6,7,8]. However, other authors have questioned the specificity of exaggerated and/or delayed TSH responses for hypothalamic lesions and have pointed out the often artificial distinction between pituitary and hypothalamic disease [10, 13, 22,26,27,28]. In particular, a delayed TSH response has been described in a patient with a mutation of the pituitary-specific transcription factor PIT1 in whom there was no evidence of hypothalamic dysfunction [29].…”
Section: Discussionmentioning
confidence: 99%
“…As illustrated by our findings, this is especially true in the de tection of STH and ACTH insufficiency. Recently developed tests of response to hypothalamic releasing factors are very useful in distinguishing anterior pituitary from hypothalamic dysfunction [4,7,17].…”
Section: Discussionmentioning
confidence: 99%